This is play : environments and interactions that engage infants and toddlers - Luckenbill, Julia; Subramaniam, Aarti; Thompson, Janet (National Association for the Education of Young Children, 2019)
Use this information and ideas in this practical book to become more intentional in your interactions with and curriculum decisions for infants, toddlers, and two-year-olds.